Popular New Orleans the Crescent City in periodicals, theme parks, and opera, 1875-2015 - Freitag, Florian (Routledge studies in cultural history, 2021)
"New Orleans is unique - which is precisely why there are many Crescent Cities all over the world: for almost 150 years, writers, artists, cultural brokers, and entrepreneurs have drawn on and simultaneously contributed to New Orleans's fame and popularity by recreating the city in popular media from literature, photographs, and plays to movies, television shows, and theme parks. Addressing students and fans of the city and of popular culture, Popular New Orleans examines three pivotal moments in the history of New Orleans in popular media: the creation of the popular image of the Crescent City during the late nineteenth century in the local-color writings published in Scribner's Monthly/Century Magazine; the translation of this image into three-dimensional immersive spaces during the twentieth century in Disney's theme parks and resorts in California, Florida, and Japan; and the radical transformation of this image following Hurricane Katrina in public performances such as Mardi Gras parades and operas. Covering visions of the Crescent City from George W. Cable's Old Creole Days stories (1873-76) to Disneyland's "New Orleans Square" (1966) to Rosalyn Story's opera Wading Home (2015), Popular New Orleans traces how popular images of New Orleans have changed from exceptional to exemplary"--